PENGGUNAAN COPPER SLAG SEBAGAI SUBTITUSI AGREGAT HALUS DAN PENAMBAHAN SIKA VISCOCRETE 8048 PADA HIGH VOLUME FLY ASH SELF COMPACTING CONCRETE (HVFA-SCC) TERHADAP KUAT TEKAN - Savira Ayu Candrika; Anggi Rahmad Zulfikar (Jurnal Vokasi Teknik Sipil, 2025)
The concept of Self-Compacting Concrete technology, combined with the use of high-volume fly ash (HVFA), has been proven to enhance the compressive strength of concrete. This increase in strength also be achieved through the utilization of copper slag, a by-product of copper smelting, as a fine aggregate replacement. This research employed an experimental method, creating cylindrical specimens of 150 x 300 mm in laboratory to evaluate the compressive strength of HVFA-SCC and determine the optimum variation of copper slag replacement in fine aggregates, targeting a concrete strength of f’c 30 MPa. Workability was tested using the slump flow and V-funnel methods. Compressive strength data were collected at the age of 14 days after curing in PDAM water. The substitution variations of copper slag were set at 0%, 10%, 20%, and 30% of fine aggregate requirement, while fly ash replaced 50% of cement requirement. The compressive strength tests results inndicated that substitutions of 0%, 10%, and 20% in 50% HVFA-SCC improved concrete strength, with the optimum variation achieved at 20% copper slag, resulting in a compressive strength of 38.57 MPa.